Biomechanical behavior of immediately placed implant using bone graft and socket shield techniques: a 3D finite element analysis - Reham A. Rashwan; Sanaa H. AbdElkader; Noha M. Elkersh; Rewaa G. AboElhassan (Head & Face Medicine)
Abstract Background Recently, several techniques for immediate implant placement have gained popularity, offering numerous advantages. These include the preservation of bone around the tooth socket and enhanced aesthetics. Nonetheless, the biomechanical behavior of implants and peri-implant tissues under immediate loading with these techniques remains uncertain. This study examines stress distribution surrounding an immediately placed implant, using socket shield and bone graft techniques compared to a healed socket. Materials and methods Cone-beam computed tomography (CBCT) scans of the anterior maxilla were used to construct finite element analysis (FEA) models. The process of modeling the implant, abutment, and provisional crown used standard tessellation language (STL) files of the original components. The implant was modeled in three clinical scenarios: a healed socket (HS), an extraction socket with bone graft (BG), and a socket shield (SS). A frictional contact (µ = 0.3) was established to simulate immediate loading. An axial load of 25.5 N and a non-axial load of 178 N at a 30° angle were applied along the implant’s long axis in a palatal direction. FEA was conducted for stress distribution analysis. Results In evaluating maximum principal, von Mises stress distribution within the cortical bone, the HS model exhibited the highest stress level, with a maximum of 125 MPa, 127 MPa, respectively. The SS model demonstrated the lowest stress, recording a maximum of 82 MPa, 90.7 MPa, respectively, while the BG model had a maximum value of 115 MPa, 116.84 MPa, respectively. When assessing the von Mises stress distribution associated with the implant, the HS model recorded the highest stress value of 385 MPa. In contrast, the BG and SS models recorded lower stress values of 252 MPa and 281 MPa, respectively. Conclusions The socket shield technique exhibits advantageous biomechanical performance under immediate loading conditions by reducing stress on peri-implant bone and implant components. These results endorse its clinical applicability but necessitate further in vivo validation.